DILEMA BIROKRASI DALAM PEMILUKADA (Studi tentang Interaksi Politik Antara Birokrasi dan Politisi Dalam Kontestasi Pemilukada Bangka Tengah Provinsi Kepulauan Bangka Belitung Tahun 2010) - , RENDY, Drs.Ratnawati, SU ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study is tracing about how the political interaction of the bureaucrats process occurred through various mobilization by Regent of the incumbent for the sake in carrying the house of a direct election in the Bangka Tengah in 2010. The phenomenon in dominating the bureaucrats has become a political machine in succession of the won from a candidate of direct election. The bureaucrats is not homogenous, neutral, and isolated from political dynamics. It is even a real most political arena in the many occurred bargaining the actors involved in any power relations. This is a qualitative research method. The subjects of this research are all Department Head, institutions and offices in Bangka Tengah District. Data collected from interviews, observation and documentation. Data analysis technique used is qualitative descriptive analysis. For easiness of description, take records and to interpretation rational aspect from the activity of the local elite and the elite bureaucracy. Thereby, the data collection is done in interviews, direct observation, and documentation process personal with actors from the elite and the elite the bureaucrats politic in Bangka Tengah District until the step of balloting calculation in direct demagogue in 2010. The result of this study showed that the bureaucrats in supporting the implementation of the district head election were not able to show its neutrality. This research has success to identification the political interaction the bureaucrats in Bangka Tengah district in 2010, that is to say kind of backing from the bureaucrats for the incumbent. Variation backing in the form of consultation, facility and information in a formal service. Form backing from the bureaucrats is common happened in middle layer until the bottom layer that is sub-district and village head, showing their backing for the incumbent. Make this situation the neutral the bureaucrats in Bangka Tengah district faded / delegated backing from the bureaucrats to the incumbent not only because they own wish but it most like the ex their loyalty for higher authority, those aimed to be first man in Bangka Tengah district. The factors that bringing on the incumbent get attracted to the bureaucrats is the way key strategic position from the those the bureaucrats have some hand in glove with the people's, beside that there is an easy access to infrastructure and public utilities used. The attracted from incumbent to the bureaucrats is clearly get good reaction from bureaucracy, the bureaucrats is like not giving free backing, there is something they want from their backing for the incumbent. The victory of incumbent will bring good aspect for them, especially the wish to occupy the functional position. Researcher catch sight of implication from polarization the bureaucrats that happened in the direct election demagogue in Bangka Tengah district in 2010. The implication that is political nomination clearly showing basic in like or dislike with the personal. This fact can be the local elite the bureaucrats that explanation involved in political practice. Elite the bureaucrats completely backing the incumbent to be demagogue. Participate in the elite the bureaucrats of political practices in direct elliptical demagogue in Bangka Tengah District in 2010 has been the polarization consist bureaucracy. Polarizations the bureaucrats in the Bangka Tengah have been undermine the value of neutral bureaucracy. This fact cans the make the justice in public service more becoming a great way off. The regent's interests in the arenas are not only to maintain an effective government and to create loyal political machine, the fact it has failed to get the success consolidation for winning the election. The party politicians' interests of the regent's supporters with the profit or benefit. And top bureaucrats' interest is to find out opportunities in order to the institution they stand on remains to survive and gets better position and higher echelon. However, there are double standards applied in the mechanism of interest contestation. On one side, the governor wants to experiment with its commitment to good governance, but on the other side, it must be willing to accommodate many interests of other actors though They against with its personal obsession.